New spider species of Coelotinae (Araneae, Amaurobiidae) from northern Thailand IV - Pakawin Dankittipakul (2018)
Two new species of Coelotinae, Draconarius suttisani sp. n. and D. promontorioides sp. n., are described and illustrated from material collected in northern Thailand. Draconarius suttisani sp. n. belongs to the venustus-group. Draconarius promontorioides sp. n. belongs to the lutulentus-group. Copyright © 2008 Magnolia Press.